Influence of Credit Risk Education on Access to Credit by Micro Enterprises in the Formal Sector in Kenya - Karimi, Ann; Baimwera, Bernard; Miluwi, Joshua (International Journal of Professional Practice, 2023)
Access to credit from financial institutions for the purpose of financing state-regulated micro-enterprises in Kenya has been largely based on personal judgment, resulting in a lack of available credit from banks and other financial organizations due to the high rate of credit default. This has severely restricted the prospects of entrepreneurs funding their enterprises. In order to address this issue, a study was conducted that investigated the influence of credit risk education on access to credit by micro-enterprises in the formal sector in Kenya. Credit risk education and access to credit were the independent and dependent variables. The study was guided by collective risk theory to hypothesize the interconnection between the variables. To accurately capture the insights of the research, a descriptive survey design was employed, with the target population being 1,215,184 formal sector micro-enterprises in Kenya recorded by the Business Registry. A sample size of 384 respondents was determined using the Cochran formula. A stratified proportionate sample technique was employed comprising eight regions in Kenya. Informed consent from respondents was acquired and confidentiality maintained in data collection. The study gathered and analyzed primary data using semi-structured questionnaires. Descriptive and inferential statistics were used from grouped data obtained from the overall Likert scale. Cronbach’s alpha was used to test reliability and factor analysis for validity. Logistic regression was applied to investigate the relationship between the study variables using advanced SPSS version 23. The results indicated that credit risk education had a positive influence on access to credit. However, the low levels of credit risk education, have hindered access to credit for financing the regulated micro-enterprises, thereby affecting the performance of the MSMEs sector. Based on these findings the study recommends that the Government of Kenya develops strategies for active engagement to promote credit risk education to enhance access to credit.